Penerapan Sustainable Living pada Rumah Tangga dengan Pembuatan Produk Kesehatan Ramah Lingkungan - Dyani Primasari Sukamdi; Mega Octavia; Muhammad Fariez Kurniawan; Pramitha Esha Nirmala Dewi; Inayati Murwani Rahayu (Universitas Muhammadiyah Semarang, 2022)
Public outrage over the Covid-19 pandemic has a detrimental effect on the habit of staying at home and contributes to increased household waste. The temporary closure of the TPTS Piyungan Yogyakarta has exacerbated the problem of garbage and household waste accumulation. Al Fatah Kindergarten, in collaboration with the School of Pharmacy Universitas Muhammadiyah Yogyakarta, wishes to encourage the community to practice environmental stewardship. The environmental conservation effort will begin at home with domestic waste management. This guidance tries to broaden the public's perception and understanding of waste. Online counseling and training are available on two primary topics: